Differences in end-of-life care and outcomes in palliative consultation-eligible patients with and without do-not-resuscitate orders: A propensity score-matched study. Issue 6 (2nd June 2021) - Chang, Julia Chia-Yu; Yang, Che; Lai, Li-Ling; Huang, Hsien-Hao; Fan, Ju-Sing; Lin, Ming-Hwai; Hsu, Teh-Fu; Yen, David Hung-Tsang
Abstract : Background: The primary objective of palliative care, not synonymous with end-of-life (EOL) care, is to align care plans with patient goals, regardless of whether these goals include the pursuit of invasive, life-sustaining procedures, or not. This study determines the differences in EOL care, resource utilization, and outcome in palliative care consultation-eligible emergency department patients with and without do-not-resuscitate (DNR) orders. Methods: This is a retrospective observational study. We consecutively enrolled all the acutely and critically ill emergency department patients eligible for palliative care consultation at the Taipei Veterans General Hospital, a 3000-bed tertiary hospital, from February 1 to July 31, 2018. The outcome measures included in-hospital mortality and EOL care of patients with and without DNR. Results: A total of 396 patients were included: 159 with and 237 without DNR. Propensity score matching revealed that patients with DNR had significantly shorter duration of hospital stay (404.4 ± 344.4 hours vs 505.2 ± 498.1 hours; p = 0.037), higher in-hospital mortality (54.1% vs 34.6%; p < 0.001), and lower total hospital expenditure (191 239 ± 177 962 NTD vs 249 194 ± 305 629 NTD; p = 0.04). Among patients with DNR, there were fewer deaths in the intensive care unit (30.2% vs 37.0%), more deaths in the hospice ward (16.3% vs 7.4%), more critical discharge to home (9.3% vs 7.4%), more endotracheal removals (3.1% vs 0%; p = 0.024), and more narcotics use (32.7% vs 22.1%; p = 0.018). Conclusion: The palliative care consultation-eligible emergency department patients with DNR compared with those without DNR experienced worse outcomes, greater pain control, more endotracheal extubations, shorter duration of hospital stay, more critical discharge to home, more hospice referrals, and 23.3% reduction in total expenditure. There were fewer deaths in the ICU among them as well.